Components/factors of the Czech version of the Physical Self Perception Profile (PSPP-CZ) among high school students [Komponenty/faktory české verze dotazníku tělesného sebepojetí (PSPP-CZ) u středoškolských studentů] - Vlastimil Kudláček; Vlastimil Kudláček jr; Martin Kudláček; Michal Kudláček (Palacky University, 2010)
BACKGROUND: The physical self has been widely investigated as a determinant of exercise behaviors as well as a contributor to mental health and well being (Fox, 1997). Self esteem has been generally accepted as an important mediator of exercise and self esteem (Fox, 2000; Sonstroem, 1997). Understanding self development processes has increased in importance as self esteem and self perception components have become increasingly valued in educational, clinical and community health programs (Ferreira & Fox, 2008). In order to examine the relationships between various levels of physical activities and self perception we need to use standardized instruments to measure physical self perception among Czech teenagers. OBJECTIVE: The purpose of this study was to analyse the structure of the translated PSPP-CZ questionnaire among the population of high school students by finding components of PSPP-CZ using principal component analysis. The Physical Self Perception Profile (PSPP) has never been used in the CZ population before. METHODS: Participants were high school students from five schools representing three kinds of high schools in the Czech Republic. Of these participants, 666 were boys and 403 were girls. The average age of the participants was 17.00 (± 1.34) in boys and 16.63 (± 1.39) in girls. Participants received a test battery containing a Czech version of PSPP (Fox, 1990). PSPP has four subscales: (a) sports competence - SPORT; (b) attractiveness of the figure - BODY; (c) physical strength and musculature - STRENGTH; and (d) physical conditioning and exercise - CONDITION (Fox, 1990). RESULTS: Data were analyzed using SPSS PC 11.0. Cronbach Alpha, representing the internal consistency measure consisted of: (a) sport subscale (males = .86, females = .86); (b) physical condition subscales (males = .82, females = .85); (c) attractiveness of figure subscales (males = .78, females = .88); and (d) strength subscale (males = .87, females = .85). Initially we have found that students from Czech high schools have a different structure of self perception then the original PSPP population from England (Fox, 1990). Our findings correspond with findings among Flemish adults (Van de Vliet et al., 2002; Ferreira & Fox, 2007) where components of sport and condition were also loaded into one factor. There are clear, subtle differences in the structure of physical self perception as related to cultural and language differences. Findings of internal reliability and content validity suggest that the three subscales questionnaire can be used in the Czech population as a valid and reliable instrument. CONCLUSIONS: In conclusion, we can recommend using the PSPP-CZ with three scales for use among young adults for the exploration of the role of physical self-perception as a determinant of physical activity/inactivity and a healthy lifestyle. [VÝCHODISKA: Tělesné sebepojetí bylo široce zkoumáno jako určující činitel pro cvičení stejně jako jeden z prvků majících vliv na duševní zdraví a blaho (Fox, 1997). Sebepojetí je všeobecně přijímáno jako významný prostředník mezi cvičením a sebeúctou (Fox, 2000; Sonstroem, 1997). Porozumění procesům seberozvoje nabylo na důležitosti, jelikož sebeúcta a sebepojetí jsou stále významnějšími komponenty vzdělávacích, klinických a komunitních programů péče o zdraví (Ferreira & Fox, 2008). Abychom mohli prozkoumat vztahy mezi různými úrovněmi tělesných aktivit a sebepojetí, musíme k měření tělesného sebepojetí mezi českými adolescenty využít standardizované nástroje. CÍLE: Účelem této studie bylo analyzovat strukturu přeloženého dotazníku PSPP-CZ mezi populací středoškolských studentů, a to hledáním komponentů PSPP-CZ za pomoci analýzy hlavních komponentů. Dotazník tělesného sebepojetí (Physical Self Perception Profi le, PSPP) na české populaci nikdy nebyl použit. METODIKA: Studie se zúčastnili středoškolští studenti z pěti škol reprezentujících tři typy škol v České republice, a to 666 chlapců a 403 dívek. Průměrný věk účastníků byl 17,00 (± 1,34) let u chlapců a 16,63 (± 1,39) let u dívek. Účastníci obdrželi soubor testů obsahující českou verzi PSPP (Fox, 1990). PSPP má čtyři subškály: a) sportovní dovednosti – SPORT; b) atraktivita postavy – TĚLO; c) fyzická síla a muskulatura – SÍLA; a d) fyzická příprava a cvičení – KONDICE (Fox, 1990). VÝSLEDKY: Údaje byly analyzovány za pomoci SPSS PC 11.0. Měřítko interní konzistence Cronbachova alfa zahrnovalo: a) subškálu sportu (muži = 0,86, ženy = 0,86); b) subškály tělesné kondice (muži = 0,82, ženy = 0,85); c) subškály atraktivity postavy (muži = 0,78, ženy = 0,88); a d) subškálu síly (muži = 0,87, ženy = 0,85). Nejprve jsme zjistili, že struktura sebepojetí u českých středoškoláků je odlišná od původní PSPP populace z Anglie (Fox, 1990). Naše zjištění korespondují s výsledky zjištěnými mezi vlámskými dospělými (Van de Vliet et al., 2002; Ferreira & Fox, 2007), kde komponenty sportu a kondice byly také součástí jednoho faktoru. Ve struktuře tělesného sebepojetí existují jasné, přesné rozdíly podmíněné kulturními a jazykovými odlišnostmi. Zjištění o interní reliabilitě a validitě obsahu naznačují, že dotazník se třemi subškálami lze u české populace použít jako účinný a spolehlivý nástroj. ZÁVĚRY: Doporučujeme použití PSPP-CZ se třemi škálami pro použití mezi mládeží ke zkoumání role tělesného sebepojetí jako určujícího činitele pohybové aktivity/neaktivity a zdravého životního stylu.]